2008
DOI: 10.1002/hup.990
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of carbamazepine and lithium in treatment of bipolar disorder: A systematic review of randomized controlled trials

Abstract: This review suggests that carbamazepine might be comparable to lithium in terms of efficacy and safety, and therefore a valuable option in the treatment of both manic and maintenance phases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(18 citation statements)
references
References 47 publications
0
18
0
Order By: Relevance
“…However, evidence pertaining to possible prophylactic, mood-stabilizing effects of carbamazepine remains limited, despite decades of international use of the drug for long term as well as antimanic treatment for bipolar disorder patients, and it is not FDA approved for long-term mood stabilization. Some evidence from controlled trials suggests that carbamazepine and lithium may have similar effects [ 81,95,96,282 ] . In addition to its main anticonvulsant effects and usefulness in bipolar disorder, carbamazepine also is effective in migraine (which is prevalent in bipolar disorder patients), neuropathic pain, and trigeminal neuralgia [ 254 ] .…”
Section: Carbamazepinementioning
confidence: 98%
“…However, evidence pertaining to possible prophylactic, mood-stabilizing effects of carbamazepine remains limited, despite decades of international use of the drug for long term as well as antimanic treatment for bipolar disorder patients, and it is not FDA approved for long-term mood stabilization. Some evidence from controlled trials suggests that carbamazepine and lithium may have similar effects [ 81,95,96,282 ] . In addition to its main anticonvulsant effects and usefulness in bipolar disorder, carbamazepine also is effective in migraine (which is prevalent in bipolar disorder patients), neuropathic pain, and trigeminal neuralgia [ 254 ] .…”
Section: Carbamazepinementioning
confidence: 98%
“…In a review of RCTs comparing carbamazepine and lithium, and combining results in meta-analyses when possible, the two were similar in efficacy for acute mania as well as in safety and the ability to prevent relapses. 141 Notably, carbamazepine is not FDA approved for long-term use, and the review found that in maintenance studies, carbamazepine patients were more likely than patients on lithium to withdraw from the studies due to adverse effects. 141 Patients with rapid cycling might benefit from adding carbamazepine to lithium: in one study, the long-term response was better with the combination than with either of the medications alone (28% response with lithium, 19% with carbamazepine, and 56% with the combination).…”
Section: Carbamazepinementioning
confidence: 98%
“…141 Notably, carbamazepine is not FDA approved for long-term use, and the review found that in maintenance studies, carbamazepine patients were more likely than patients on lithium to withdraw from the studies due to adverse effects. 141 Patients with rapid cycling might benefit from adding carbamazepine to lithium: in one study, the long-term response was better with the combination than with either of the medications alone (28% response with lithium, 19% with carbamazepine, and 56% with the combination). 142 A similar study found better results with the combination but more side effects and increased need for additional adjunctive medications.…”
Section: Carbamazepinementioning
confidence: 98%
“…67 Controlled studies against placebo, lithium, and antipsychotic drugs showed that carbamazepine is equivalent to lithium in treating acute mania [68][69][70] and may represent a valid alternative for lithium-refractory patients, such as those with rapid fluctuations (rapid cyclers). 71,72 Data about oxcarbazepine are limited and are definitely less conclusive than those regarding carbamazepine.…”
Section: What Is the Role Of Antiepileptic Drugs?mentioning
confidence: 99%